The Role of Financial Literacy in Moderating the Relationship between Financial Behavior and Investment Decisions of Indonesian Women Investors - Nurul Sani; Paramita, Veronika Santi (Moneta : Journal of Economics and Finance, 2024)
The investment market in Indonesia has shown significant improvement in recent years, with the participation of female investors dominating. However, this phenomenon is not comparable to the high number of victims of illegal investment, which women also dominate. This study examines how financial literacy affects the relationship experienced by regret, herding behaviour, and risk tolerance when making investing decisions. This study employs a quantitative methodology with a cohort of Indonesian women investors who fit specific requirements. One hundred respondents were selected using the judgmental sampling technique. To analyse the data, Moderated Regression Analysis was used (MRA). The research results show that experienced regret, herding behaviour, and risk tolerance positively influence investment decisions. Apart from that, financial literacy has been proven to moderate the relationship between experienced regret, herding behaviour, and risk tolerance on investment decisions among female investors in Indonesia. These findings shed crucial light on how financial literacy may mitigate the variables influencing Indonesian women investors' investment choices.